Motivating mobility: designing for lived motivation in stroke rehabilitation - Balaam, Madeline; Rennick Egglestone, Stefan; Fitzpatrick, Geraldine; Rodden, Tom; Hughes, A.M.; Wilkinson, Anna; Nind, Thomas; Axelrod, Lesley; Harris, Eric; Ricketts, Ian; Mawson, Sue; Burridge, Jane (ACM Press, 2011)
How to motivate and support behaviour change through design is becoming of increasing interest to the CHI community. In this paper, we present our experiences of building systems that motivate people to engage in upper limb rehabilitation exercise after stroke. We report on participatory design work with four stroke survivors to develop a holistic understanding of their motivation and rehabilitation needs, and to construct and deploy engaging interactive systems that satisfy these. We reflect on the limits of motivational theories in trying to design for the lived experience of motivation and highlight lessons learnt around: helping people articulate what motivates them; balancing work, duty, fun; supporting motivation over time; and understanding the wider social context. From these we identify design guidelines that can inform a toolkit approach to support both scalability and personalisability.